The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21218207
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interaction of Protein-Pigment C-Phycocyanin with Bovine Serum Albumin in a Gomphosis Structure Inhibiting Amyloid Formation

Abstract: Accumulation of amyloid fibrils in organisms accompanies many diseases. Natural extracts offer an alternative strategy to control the process with potentially fewer side effects. In this study, the inhibition of C-phycocyanin from Spirulina sp. on amyloid formation of bovine serum albumin (BSA) during a 21-day incubation was investigated using fluorescence and circular dichroism (CD), and mechanisms were explored via kinetic fitting and molecular docking. C-phycocyanin (0–50 µg/mL) hindered the amyloid formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Scientific evidence has shown the positive effects of Spirulina in AD ( Figure 2 ). In a recent work, Luo and Jing demonstrated that C-PC is able to hinder the amyloid formation process of bovine serum albumin (BSA), inhibiting conformational conversion (α-helices and β-sheets) of BSA [ 136 ].…”
Section: Beneficial Effects Of Spirulina In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Scientific evidence has shown the positive effects of Spirulina in AD ( Figure 2 ). In a recent work, Luo and Jing demonstrated that C-PC is able to hinder the amyloid formation process of bovine serum albumin (BSA), inhibiting conformational conversion (α-helices and β-sheets) of BSA [ 136 ].…”
Section: Beneficial Effects Of Spirulina In Neurodegenerative Diseasesmentioning
confidence: 99%
“…C-PC was shown to interact with and inhibit the activity of α-synuclein and β-secretase, which are involved in fibril formation associated with Alzheimer’s and Parkinson’s disease [ 35 , 36 ]. By forming interactions with BSA, C-PC can also inhibit the formation of BSA fibrils [ 37 ]. This study provides insights into the types of molecules that can bind to this bioactive protein and stabilise its tertiary structure at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible therapeutic targets include lowering the Aβ load, which can be accomplished by hindering Aβ formation [64]. Luo and Jing (2020) [65] showed that phycocyanin (0.5-50 µg/mL) from Spirulina sp. spontaneously inhibits the Aβ formation process of bovine serum albumin (BSA) by interacting in a gomphosis structure.…”
Section: Cyanobacteria Against Alzheimer's Diseasementioning
confidence: 99%